Rapid turbidimetric assay for quantification of fusidic acid in a dermatological cream - Curbete, Mariane MacHado [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Elsevier, 2016)
Fusidic acid is an antibiotic steroid widely used for the treatment of serious infections caused by methicillin-resistant Staphylococcus aureus (MRSA) strains. Microbiological methods are indispensable to determine the mean percentage of antimicrobial in medicaments during manufacturing and quality control processes. The aim of this study was to develop and validate a microbiological method for the quantification of fusidic acid in dermatological cream by turbidimetry, using Staphylococcus epidermidis (ATCC 12228) and casoy broth as the culture medium. The validation parameters were in accordance with ICH specifications and demonstrated accuracy, precision, selectivity, and robustness, with linear ranges from 0.25 to 2.25 μg mL-1. This method is an alternative to the diffusion agar assay currently employed to quantify fusidic acid in dermatological cream, since it is sensitive, fast, and more economical.
Keywords: Antibiotic; Fusidic acid; Quality control; Turbidimetric assay; Validation